Modelling of Risk Management for Product Development of Yogurt Drink Using House of Risk (HOR) Method - Wahyudin, Nur Eko; Santoso, Imam (The Asian Journal of Technology Management (AJTM), 2016)
Abstract. Product Development is essential for the company to stay steady or advance in the market competition. However, the main challenge in product development is associated with the uncertaincy risks that may appeared during the design process. Such risks may affect the success rate  of the product development and may contribute either to a small or a huge loss, in  which the sustainability of the company can also be affected. To mitigate the risks in product development, risk management is critical. CV. XYZ is a company producing dairy-based products such as mozzarella cheese and yogurt. This research is aimed to identify the potential appeared risks, to arrange the priority  order of risk agents and to conceptualize the risk mitigation strategy to be applied. A Yogurt drink product development is needed by CV. XYZ to support the company goals of the product and market expansion. House of Risk (HOR) method was used in this research. Two phases included in the identification process, namely marketing and product development design. The research results have examined  20 risks with 27 identified risk agents. Using the Aggregate Risk Potential (ARP) value, and Pareto 80:20 principal, this study provides a strategic guideline as how to mitigate the top-three identified risk agents.                                                                                                                      Keywords: House of Risk (HOR), Risk Management, Product Development, Yogurt Drink